-x(2x-8)-5x=0

Simple and best practice solution for -x(2x-8)-5x=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -x(2x-8)-5x=0 equation:



-x(2x-8)-5x=0
We add all the numbers together, and all the variables
-5x-x(2x-8)=0
We multiply parentheses
-2x^2-5x+8x=0
We add all the numbers together, and all the variables
-2x^2+3x=0
a = -2; b = 3; c = 0;
Δ = b2-4ac
Δ = 32-4·(-2)·0
Δ = 9
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{9}=3$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(3)-3}{2*-2}=\frac{-6}{-4} =1+1/2 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(3)+3}{2*-2}=\frac{0}{-4} =0 $

See similar equations:

| -8u-4=4u+12 | | 8^2+32x+30=0 | | -5y-19=-3(y+1) | | x/6=12/x | | 9(y-2)=2y-46 | | 4c+7c=$1.50 | | r=99/3 | | -3x+20=-60x-20 | | 3/4x=1/8x-6=15 | | (y-6/y)-6/y=(y+6)/(y-6) | | 5-4x=8x+6 | | 3x=6 7 | | F(z)=2z-8/7z+2 | | x^2-12x+67=0 | | 0.3=0.5^x | | 3x-3+22=4x-1+9x | | 3.6=1.2r | | -3(k-1)=3(k+1)-48 | | 4x-2(2-3x)=4(x-4)-6 | | 8y-4×=12 | | 4(k-4)-3(k+1)-14=-26 | | X+x+6=20-x | | x^2+10x-24=-9 | | 3x-3+22=5x-1+8x | | 25-3x=5+x | | 12P=3b^2 | | -5(3w+1)-w=43 | | 0=28x-3x^2 | | n+7/9=17/18 | | 9k×96=98;K= | | -500x(2x-9)=0 | | 4x=9x-2 |

Equations solver categories